Educational Socialization on the Importance of Saving from an Early Age as Preparation for the Future for Students of SD Negeri 1 Lalowosula - Muh. Pariama; Febri Hariyanto; Dandung Pamungkas; Muh. Rahmad Saputra; Sarina S; Elma E; Sastril S; Masrah M; Astrid Wulandari; Niken Juniasih (Yayasan Daarul Huda Kruengmane, 2026)
Saving activities from an early age are a form of character education that helps develop frugality, responsibility, and independence in children. This study aims to examine the importance of saving education for early childhood, effective methods for teaching it, and its impact on children’s character development. The research method used is descriptive qualitative with a literature study approach. The results show that saving habits taught through play-based approaches, hands-on practice, and parental role modeling are able to foster financial awareness and a sense of responsibility in children regarding the use of money. Therefore, saving education from an early age is very important to be implemented both in the family and school environments, particularly at SD Negeri 1 Lalowosula.